2020
DOI: 10.1097/dad.0000000000001551
|View full text |Cite
|
Sign up to set email alerts
|

BAP-1 Expression Status by Immunohistochemistry in Cellular Blue Nevus and Blue Nevus–like Melanoma

Abstract: The family of blue nevi includes the common blue nevus (BN), cellular blue nevus (CBN), and atypical BN, while melanomas with BN-like morphology can either arise in association with a blue nevus (MABN) or in the de novo setting mimicking cellular blue nevus (MMCBN). Recent molecular and immunohistochemical studies have demonstrated loss of BAP-1 in MABN/MMCBN but not in BN/CBN, suggesting that loss of BAP-1 correlates with a malignant phenotype in these lesions. In this study, we applied anti–BAP-1 antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…showed that 64% (7/11) of MBNs lacked immunohistochemical BAP‐1 nuclear expression, whereas none (0/24) of the CBNs in their cohort showed loss of immunohistochemical BAP‐1 nuclear expression. Similar results were also obtained in a recent study by Chen et al 32 …”
Section: Melanocytic Lesions With Bn‐like (Dendritic) Morphologysupporting
confidence: 92%
See 2 more Smart Citations
“…showed that 64% (7/11) of MBNs lacked immunohistochemical BAP‐1 nuclear expression, whereas none (0/24) of the CBNs in their cohort showed loss of immunohistochemical BAP‐1 nuclear expression. Similar results were also obtained in a recent study by Chen et al 32 …”
Section: Melanocytic Lesions With Bn‐like (Dendritic) Morphologysupporting
confidence: 92%
“…Furthermore, CBNs lack β‐catenin nuclear expression, 30 which is a useful immunophenotypic feature that helps to distinguish CBNs from one of their histological mimics, deep penetrating naevus (DPN) (see below for more details). BAP‐1 nuclear expression is almost always preserved in CBNs 31,32 . This contrasts with melanomas with BN‐like morphology (see below for more details), some of which can show loss of BAP‐1 nuclear expression 31,32 .…”
Section: Melanocytic Lesions With Bn‐like (Dendritic) Morphologymentioning
confidence: 92%
See 1 more Smart Citation
“…3 Recently, Costa et al 4 reported that loss of nuclear BAP1 expression strongly supported the diagnosis of melanomas associated with BN; however, a case of cellular BN with BAP1 loss was also reported. 5 In the present case, extremely unique features of both benign (low atypia and mitosis, and low MIB-1 reactivity) and malignancy (loss of BAP1 and abnormal FDG uptake) led to difficulty in diagnosis. Future studies investigating the accuracy of BAP1 staining and PET/CT to make a correct diagnosis of subcutaneous mass developed in PTBN with a large sample size are required.…”
mentioning
confidence: 63%
“…Recently, Costa et al 4 . reported that loss of nuclear BAP1 expression strongly supported the diagnosis of melanomas associated with BN; however, a case of cellular BN with BAP1 loss was also reported 5 …”
Section: Figurementioning
confidence: 96%